Compound and polymer composition containing the compound

By combining the compound with the polymer with the structural monomer of the photo-induced activation species, the crosslinked structure is solved, and the problem of insufficient adhesion and retention of the existing adhesive is significantly improved, and the adhesive properties and contamination resistance are significantly improved.

CN115135677BActive Publication Date: 2025-04-29MITSUBISHI CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202180016178.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-24
Filing Date
2021-03-17
Publication Date
2025-04-29
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

The adhesive and retaining force of the adhesive obtained in the prior art are insufficient.

Method used

A compound is used, which contains two or more structural units from monomer M with radical polymerizable groups, and has a radical polymerizable group A at the end, and a monomer M contains a monomer m, and a monomer m has a structure to generate an active species excited by light.

Benefits of technology

By combining the compound with the polymer, a crosslinked structure is formed, which significantly improves the adhesion, retention and substrate pollution resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003809806160000021
    Figure BDA0003809806160000021
  • Figure BDA0003809806160000031
    Figure BDA0003809806160000031
  • Figure BDA0003809806160000051
    Figure BDA0003809806160000051
Patent Text Reader

Abstract

A compound comprising two or more structural units derived from a monomer M having a radical polymerizable group and having a radical polymerizable group A at a terminal, wherein the monomer M comprises a monomer m having a structure that generates an active species when excited by light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a compound which can effectively improve the adhesion, holding power and other properties of an adhesive, and a polymer composition containing the compound.

[0002] This application claims priority based on Japanese Patent Application No. 2020-53216 filed in Japan on March 24, 2020, the contents of which are incorporated herein by reference. Background Art

[0003] Compounds that form cross-linked structures with polymers are used to improve physical properties in various applications such as coatings, films, molding materials, adhesives, and bonding agents.

[0004] For example, Patent Document 1 describes a pressure-sensitive adhesive sheet comprising a (meth)acrylic copolymer having a radiation-reactive site and a plasticizer capable of forming a bond with the (meth)acrylic copolymer upon irradiation with radiation.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2013-40256 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the adhesive force and holding power of the adhesive obtained by the method described in Patent Document 1 are insufficient. An object of the present invention is to solve these problems.

[0010] Technical solutions to the problem

[0011] The first gist of the present invention is a compound comprising two or more structural units derived from a monomer M having a radical polymerizable group and having a radical polymerizable group A at the end, wherein the monomer M comprises a monomer m having a structure that generates an active species when excited by light.

[0012] The second gist of the present invention is a polymer composition comprising the compound and a polymer.

[0013] The third gist of the present invention is a (meth)acrylic copolymer comprising a structural unit derived from a monomer m having a structure that generates an active species when excited by light.

[0014] The fourth gist of the present invention is a polymer composition comprising the (meth)acrylic copolymer and a compound.

[0015] A fifth gist of the present invention is an adhesive obtained by irradiating the polymer composition with ultraviolet rays.

[0016] A sixth aspect of the present invention is a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer contains the polymer composition.

[0017] A seventh aspect of the present invention is a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer contains the pressure-sensitive adhesive irradiated with ultraviolet rays.

[0018] The present invention has the following aspects: [1]

[0020] A compound comprising two or more structural units derived from a monomer M having a radical polymerizable group and having a radical polymerizable group A at a terminal, wherein the monomer M comprises a monomer m having a structure that generates an active species when excited by light. [2]

[0022] The compound according to [1], wherein the active species generated by light excitation is a free radical. [3]

[0024] The compound according to [1] or [2], wherein the monomer m has a structure represented by the following Formula 1:

[0025] [Chemistry 1]

[0026]

[0027] In the formula, R A , RB each independently represent an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group. [4]

[0029] The compound according to [1] to [3], wherein the content of the structural unit derived from the monomer m in the compound is preferably 0.01 mass % to 50 mass % and more preferably 5 mass % to 40 mass % relative to the total mass of the compound. [5]

[0031] The compound according to [1] to [4], wherein the monomer M contains a (meth)acrylate having an alicyclic structure. [6]

[0033] The compound according to [1] to [5], wherein the weight average molecular weight measured by gel permeation chromatography is preferably 1,000 or more and 100,000 or less, and more preferably 2,000 or more and 50,000 or less. [7]

[0035] The compound according to [1] to [6], which has a structure represented by the following Formula 2:

[0036] [Chemistry 2]

[0037]

[0038] In the formula, R is a group having a structure that generates an active species when excited by light, or a linear or branched alkyl group having 1 to 30 carbon atoms, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, or an unsubstituted or substituted heterocyclic group; Z is a terminal group; multiple R 21 Each independently represents a hydrogen atom or a methyl group; multiple R 22 Each independently represents a group having a structure that generates an active species when excited by light, an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, an unsubstituted or substituted heteroaryl group, an unsubstituted or substituted aralkyl group, an unsubstituted or substituted alkaryl group, an unsubstituted or substituted organosilyl group or an unsubstituted or substituted (poly)organosiloxane group, and the substituents in these groups are at least one selected from an alkyl group, an aryl group, a heteroaryl group, a non-aromatic heterocyclic group, an aralkyl group, an alkaryl group, a carboxyl group, an alkoxycarbonylalkyl group, an alkylcarbonyloxyalkyl group, an epoxy group, a hydroxyl group, an alkoxy group, a primary amino group, a secondary amino group, a tertiary amino group, an isocyanate group, a sulfonic acid group and a halogen atom; and n represents a natural number of 2 or greater. [8]

[0040] The compound according to [5], wherein the alicyclic structure includes cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, etc. In addition, the polycyclic alicyclic group is norbornyl, isobornyl, tricyclononyl, tricyclodecyl or tetracyclododecyl. [9]

[0042] The compound according to [1] to [8], wherein in Formula 2, R or multiple R 22 At least one of the groups is a group having a structure that generates an active species when excited by light.

[10]

[0044] The compound according to [1] to [9], wherein the monomer m is 4-acryloxybenzophenone, 4-methacryloxybenzophenone, 4-[2-(acryloxy)ethoxy]benzophenone, 4-[2-(methacryloxy)ethoxy]benzophenone, 2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-4-(2-acryloxy)ethoxybenzophenone, 2-hydroxy-4-(2-methyl-2-acryloxy)ethoxybenzophenone, 2-hydroxy-4-acryloxy-5-tert-butylbenzophenone or 2-hydroxy-4-acryloxy-2',4'-dichlorobenzophenone.

[11]

[0046] A polymer composition comprising the compound described in any one of [1] to

[10] and a polymer other than the compound.

[12]

[0048] The polymer composition according to

[11] , wherein the polymer has a glass transition temperature of 0°C or less.

[13]

[0050] The polymer composition according to

[11] or

[12] , wherein the polymer is a (meth)acrylic copolymer.

[14]

[0052] The polymer composition according to

[13] , wherein the (meth)acrylic copolymer comprises a structural unit derived from a monomer represented by the following Formula 1:

[0053] [Chemistry 3]

[0054]

[0055] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group.

[15]

[0057] The polymer composition according to

[13] or

[14] , wherein the (meth)acrylic copolymer contains a structural unit derived from a carboxyl group-containing (meth)acrylic monomer.

[16]

[0059] The polymer composition according to

[15] , wherein the carboxyl group-containing (meth)acrylic monomer is (meth)acrylic acid, 2-(meth)acryloxyethylhexahydrophthalic acid, 2-(meth)acryloxypropylhexahydrophthalic acid, 2-(meth)acryloxyethylphthalic acid, 2-(meth)acryloxypropylphthalic acid, 2-(meth)acryloxyethylmaleic acid, 2-(meth)acryloxypropylmaleic acid, 2-(meth)acryloxyethylsuccinic acid or 2-(meth)acryloxypropylsuccinic acid.

[17]

[0061] The polymer composition according to

[15] or

[16] , wherein the content of the structural unit derived from the carboxyl group-containing (meth)acrylic monomer is preferably 0.1 to 20% by mass, preferably 0.5 to 10% by mass, and more preferably 1 to 6% by mass, relative to the total mass of the (meth)acrylic copolymer.

[18]

[0063] The polymer composition according to

[13] to

[17] , wherein the weight average molecular weight (Mw) of the (meth)acrylic copolymer measured by gel permeation chromatography (GPC) is preferably 5,000 to 2,000,000, more preferably 10,000 to 1,000,000, and even more preferably 30,000 to 350,000.

[19]

[0065] The polymer composition according to

[13] to

[18] , wherein the glass transition temperature (Tg) of the (meth)acrylic copolymer is preferably -100°C to 0°C, more preferably -80°C to -5°C.

[20]

[0067] The polymer composition according to

[11] to

[19] , wherein the ratio (mass ratio) of the compound to the polymer is preferably in the range of 1:3 to 0.5:99.5, and preferably 1:9 to 1:70. [twenty one]

[0069] The polymer composition according to any one of

[11] to

[20] , wherein when forming an adhesive layer, the melt viscosity when measured at 130° C. and a frequency of 0.02 Hz is preferably 10 to 300 Pa·s, more preferably 20 to 200 Pa·s. [twenty two]

[0071] The polymer composition according to any one of

[11] to

[21] , wherein when forming an adhesive layer, the peel strength (N / 25 mm) is preferably 5 to 20 N / 25 mm, more preferably 10 to 17 N / 25 mm. [twenty three]

[0073] The polymer composition according to any one of

[11] to

[22] , wherein an adhesive layer is formed and bonded to a SUS plate, and the holding time when a load of 1.0 kg is applied downward at 40°C with the other side of the adhesive layer preferably is 50,000 seconds or more, more preferably 86,400 seconds or more. [twenty four]

[0075] The polymer composition according to

[11] to

[23] , wherein an adhesive layer is formed and bonded to a SUS plate, and the holding time when a load of 1.0 kg is applied downward to the other side of the adhesive layer at 80°C is preferably 1500 seconds or more, more preferably 3000 seconds or more, and even more preferably 20000 seconds or more.

[25]

[0077] The polymer composition according to

[11] to

[24] , wherein an adhesive layer is formed and adhered to a SUS plate, and when the adhesive layer is peeled off, the residual adhesive area relative to the surface area of ​​the SUS plate is preferably greater than 0 area % and less than 20 area %, and more preferably 0 area %.

[26]

[0079] Use of the polymer composition described in

[11] to

[25] in the production of an adhesive composition.

[27]

[0081] An adhesive composition comprising the polymer composition described in

[11] to

[25] .

[28]

[0083] An adhesive obtained by irradiating the adhesive composition described in

[27] with ultraviolet rays.

[29]

[0085] The adhesive according to

[28] , wherein the irradiation energy of the ultraviolet rays is preferably 10 mJ / cm 2 Above and 500mJ / cm 2 Below, more preferably 20mJ / cm 2 Above and 300mJ / cm 2 the following.

[30]

[0087] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer comprises the pressure-sensitive adhesive composition described in

[27] .

[31]

[0089] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, the pressure-sensitive adhesive comprising the pressure-sensitive adhesive irradiated with ultraviolet rays according to

[28] or

[29] .

[32]

[0091] A (meth)acrylic copolymer includes a structural unit derived from a monomer m, wherein the monomer m has a structure that generates an active species when excited by light.

[33]

[0093] The (meth)acrylic copolymer according to

[32] , wherein the monomer m is a monomer represented by the following formula 1:

[0094] [Chemistry 4]

[0095]

[0096] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group.

[34]

[0098] The (meth)acrylic copolymer according to

[32] or

[33] , wherein the (meth)acrylic copolymer contains a structural unit derived from a carboxyl group-containing (meth)acrylic monomer.

[35]

[0100] The (meth)acrylic copolymer according to

[34] , wherein the carboxyl-containing (meth)acrylic monomer is (meth)acrylic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, 2-(meth)acryloyloxyethylphthalic acid, 2-(meth)acryloyloxypropylphthalic acid, 2-(meth)acryloyloxyethylmaleic acid, 2-(meth)acryloyloxypropylmaleic acid, 2-(meth)acryloyloxyethylsuccinic acid or 2-(meth)acryloyloxypropylsuccinic acid.

[36]

[0102] The (meth)acrylic copolymer according to

[34] or

[35] , wherein the content of the structural unit derived from the carboxyl group-containing (meth)acrylic monomer is preferably 0.1 to 20% by mass, preferably 0.5 to 10% by mass, and more preferably 1 to 6% by mass, relative to the total mass of the (meth)acrylic copolymer.

[37]

[0104] The (meth)acrylic copolymer according to

[32] to

[36] , wherein the weight average molecular weight (Mw) of the (meth)acrylic copolymer measured by gel permeation chromatography (GPC) is preferably 5,000 to 2,000,000, more preferably 10,000 to 1,000,000, and even more preferably 30,000 to 350,000.

[38]

[0106] The (meth)acrylic copolymer according to

[32] to

[37] , wherein the glass transition temperature (Tg) of the (meth)acrylic copolymer is preferably -100°C to 0°C, and more preferably -80°C to -5°C.

[39]

[0108] A polymer composition comprising the (meth)acrylic copolymer described in any one of

[32] to

[38] and a compound having a radical polymerizable group A at the terminal and containing two or more structural units derived from a monomer M; the monomer M having a radical polymerizable group.

[40]

[0110] The polymer composition according to

[39] , wherein the ratio (mass ratio) of the compound to the polymer is preferably in the range of 1:3 to 0.5:99.5, and preferably 1:9 to 1:70.

[41]

[0112] The polymer composition according to

[39] or

[40] , wherein when forming an adhesive layer, the melt viscosity when measured at 130° C. and a frequency of 0.02 Hz is preferably 10 to 300 Pa·s, more preferably 20 to 200 Pa·s.

[42]

[0114] The polymer composition according to

[39] to

[41] , wherein when forming an adhesive layer, the peel strength (N / 25 mm) is preferably 5 to 20 N / 25 mm, more preferably 10 to 17 N / 25 mm.

[43]

[0116] The polymer composition according to

[39] to

[42] , wherein an adhesive layer is formed and bonded to a SUS plate, and the holding time when a load of 1.0 kg is applied downward at 40°C with the other side of the adhesive layer preferably is 50,000 seconds or more, more preferably 86,400 seconds or more.

[44]

[0118] The polymer composition according to

[39] to

[43] , wherein an adhesive layer is formed and bonded to a SUS plate, and the holding time when a load of 1.0 kg is applied downward to the other side of the adhesive layer at 80°C is preferably 1500 seconds or more, more preferably 3000 seconds or more, and further preferably 20000 seconds or more.

[45]

[0120] The polymer composition according to

[39] to

[44] , wherein an adhesive layer is formed and adhered to a SUS plate, and when the adhesive layer is peeled off, the residual adhesive area relative to the surface area of ​​the SUS plate is preferably greater than 0 area % and less than 20 area %, and more preferably 0 area %.

[46]

[0122] Use of the polymer composition described in

[39] to

[45] in the production of an adhesive composition.

[47]

[0124] An adhesive composition comprising the polymer composition described in

[39] to

[45] .

[48]

[0126] An adhesive obtained by irradiating the adhesive composition described in

[47] with ultraviolet rays.

[49]

[0128] The adhesive according to

[48] , wherein the irradiation energy of the ultraviolet rays is preferably 10 mJ / cm 2 Above and 500mJ / cm 2 Below, more preferably 20mJ / cm 2 Above and 300mJ / cm 2 the following.

[50]

[0130] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive layer comprises the pressure-sensitive adhesive composition described in

[47] .

[51]

[0132] A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer, the pressure-sensitive adhesive comprising the pressure-sensitive adhesive irradiated with ultraviolet rays according to

[48] or

[49] .

[0133] Effects of the Invention

[0134] When the compound or (meth)acrylic copolymer of the present invention is used as a component of a polymer composition, it improves adhesive strength, holding power, and substrate stain resistance. DETAILED DESCRIPTION

[0135] Compounds

[0136] The compound of the present invention is a compound comprising two or more structural units derived from a monomer M having a radical polymerizable group and having a radical polymerizable group A at a terminal, wherein the monomer M includes a monomer m having a structure that generates an active species when excited by light.

[0137] The compound of the present invention can form a cross-linked structure with other polymers by having a radical polymerizable group A at the terminal.

[0138] Furthermore, the compound of the present invention can also be polymerized with other monomers to obtain a graft copolymer by having a radical polymerizable group A at the terminal.

[0139] The radical polymerizable group A is preferably a group having an ethylenically unsaturated bond. Examples of the group having an ethylenically unsaturated bond include CH2=C(COOR)-CH2-, (meth)acryloyl group, 2-(hydroxymethyl)acryloyl group, and vinyl group.

[0140] Here, R represents a hydrogen atom, an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, or an unsubstituted or substituted heterocyclic group.

[0141] The unsubstituted or substituted alkyl group is preferably an unsubstituted or substituted alkyl group having 1 to 30 carbon atoms, more preferably an unsubstituted or substituted alkyl group having 1 to 20 carbon atoms, and still more preferably an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms.

[0142] The unsubstituted or substituted alicyclic group is preferably an unsubstituted or substituted alicyclic group having 3 to 30 carbon atoms, more preferably an unsubstituted or substituted alicyclic group having 3 to 20 carbon atoms, and still more preferably an unsubstituted or substituted alicyclic group having 3 to 10 carbon atoms.

[0143] The unsubstituted or substituted aryl group is preferably an unsubstituted or substituted aryl group having 6 to 30 carbon atoms, more preferably an unsubstituted or substituted aryl group having 6 to 20 carbon atoms, and still more preferably an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.

[0144] The unsubstituted or substituted heterocyclic group is preferably an unsubstituted or substituted heterocyclic group having 3 to 30 carbon atoms, more preferably an unsubstituted or substituted heterocyclic group having 3 to 20 carbon atoms, and still more preferably an unsubstituted or substituted heterocyclic group having 3 to 10 carbon atoms.

[0145] In addition, the compound of the present invention needs to include a structural unit derived from a monomer m having a structure that generates an active species when excited by light.

[0146] The compound of the present invention has a structure that generates active species when excited by light. For example, the compound of the present invention can be mixed with other polymers and then irradiated with ultraviolet rays to form a cross-linked structure.

[0147] The structure that generates active species by light excitation means a structure that generates any of radicals, cations, and anions by irradiation with ultraviolet rays, electron beams, etc., and preferably a structure that generates radicals from the viewpoint of reactivity.

[0148] Examples of the monomer having a structure that generates radicals when excited by light include monomers having a benzophenone skeleton, a thioxanthone skeleton, an anthraquinone skeleton, and the like. From the viewpoint of reactivity, a benzophenone derivative represented by the following formula 1 is preferred.

[0149] Examples of the monomer represented by the following formula 1 include 4-acryloxybenzophenone, 4-methacryloxybenzophenone, 4-[2-(acryloxy)ethoxy]benzophenone, 4-[2-(methacryloxy)ethoxy]benzophenone, 2-hydroxy-4-acryloxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone, 2-hydroxy-4-(2-acryloxy)ethoxybenzophenone, 2-hydroxy-4-(2-methyl-2-acryloxy)ethoxybenzophenone, 2-hydroxy-4-acryloxy-5-tert-butylbenzophenone, and 2-hydroxy-4-acryloxy-2',4'-dichlorobenzophenone. Particularly preferred are 4-methacryloxybenzophenone and 4-[2-(methacryloxy)ethoxy]benzophenone.

[0150] [Chemistry 5]

[0151]

[0152] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group.

[0153] Relative to the total mass of the compound, the content of the structural unit from the monomer m in the compound of the present invention is preferably 0.01% by mass or more and 50% by mass or less. From the perspective of improving the holding power when used as a polymer composition, the content of the structural unit from the monomer m in the compound is preferably a high content, and from the perspective of compatibility with other components, it is preferably a low content. From the perspective of obtaining a performance balance, the content of the structural unit from the monomer m in the compound is more preferably 1% by mass or more and 40% by mass or less.

[0154] In addition, in this specification, the content of a structural unit can be calculated from the input amount of the monomer which comprises a structural unit.

[0155] In formula 1, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom.

[0156] The alkyl group is preferably a linear or branched alkyl group having 1 to 10 carbon atoms, and more preferably a linear or branched alkyl group having 1 to 5 carbon atoms.

[0157] The alkoxy group is preferably a linear or branched alkoxy group having 1 to 10 carbon atoms, and more preferably a linear or branched alkoxy group having 1 to 5 carbon atoms.

[0158] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

[0159] n is an integer of 0 to 5, preferably 0 to 3, and more preferably 0.

[0160] m is an integer of 0 to 4, preferably 0 to 3, and more preferably 0.

[0161] X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group. The alkylene group in the (meth)acryloyloxyalkyleneoxy group is preferably an alkylene group having 2 to 10 carbon atoms, and more preferably an alkylene group having 2 to 6 carbon atoms. Examples of the (meth)acryloyloxyalkyleneoxy group include 2-(meth)acryloyloxyethoxy and 2-(meth)acryloyloxypropoxy groups.

[0162] In addition, as monomers other than the monomer m contained in the monomer M, there can be cited: hydrocarbon-containing (meth)acrylates, hydroxyl-containing (meth)acrylates, carboxyl-containing vinyl monomers, anhydride-containing vinyl monomers, unsaturated dicarboxylic acid diester monomers, epoxy-containing vinyl monomers, vinyl monomers such as vinyl propionate, and multifunctional vinyl monomers, etc.

[0163] In the hydrocarbon group-containing (meth)acrylate, the hydrocarbon group is preferably an unsubstituted or substituted hydrocarbon group having 1 to 30 carbon atoms, preferably an unsubstituted or substituted hydrocarbon group having 1 to 20 carbon atoms, and preferably an unsubstituted or substituted hydrocarbon group having 1 to 10 carbon atoms. For example, the hydrocarbon group is preferably a linear or branched alkyl group, a linear or branched alkenyl group, a linear or branched alkynyl group, a linear or branched cycloalkyl group, or a linear or branched aryl group.

[0164] For example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, isooctyl (meth)acrylate, hexadecyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, cyclohexyl (meth)acrylate, Ester, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, 3,5,5-trimethylcyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, terpene acrylate and its derivatives, hydrogenated rosin acrylate and its derivatives, behenyl (meth)acrylate and other hydrocarbon-containing (meth)acrylates; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glyceryl (meth)acrylate and other hydroxyl-containing (Meth)acrylates; (meth)acrylic acid, 2-(meth)acryloyloxyethylhexahydrophthalic acid, 2-(meth)acryloyloxypropylhexahydrophthalic acid, 2-(meth)acryloyloxyethylphthalic acid, 2-(meth)acryloyloxypropylphthalic acid, 2-(meth)acryloyloxyethylmaleic acid, 2-(meth)acryloyloxypropylmaleic acid, 2-(meth)acryloyloxyethylsuccinic acid, 2-(meth)acryloyloxypropylsuccinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, monomethyl maleate, monoethyl maleate, monooctyl maleate, monomethyl itaconate, monoethyl itaconate, monobutyl itaconate, monomethyl itaconate Carboxyl-containing vinyl monomers such as octyl ester, monomethyl fumarate, monoethyl fumarate, monobutyl fumarate, monooctyl fumarate, and monoethyl citrate; anhydride-containing vinyl monomers such as maleic anhydride and itaconic anhydride; unsaturated dicarboxylic acid diester monomers such as dimethyl maleate, dibutyl maleate, dimethyl fumarate, dibutyl fumarate, dibutyl itaconate, and diperfluorocyclohexyl fumarate; epoxy-containing vinyl monomers such as glycidyl (meth)acrylate, α-ethyl glycidyl (meth)acrylate, and 3,4-epoxybutyl (meth)acrylate; amino-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate;(Meth)acrylamide, N-tert-butyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-isopropyl acrylamide, hydroxyethyl acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone acrylamide, maleamide, maleimide and other vinyl monomers containing amide groups; styrene, α-methylstyrene, vinyltoluene, (meth)acrylonitrile, vinyl acetate, vinyl propionate and other vinyl monomers; divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, Multifunctional vinyl monomers such as diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, triallyl cyanurate, diallyl maleate, polypropylene glycol diallyl ether, and N,N'-methylenebis(meth)acrylamide;Acryloylmorpholine, polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, n-butoxyethyl (meth)acrylate, isobutoxyethyl (meth)acrylate, tert-butoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, nonylphenoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, acetoxyethyl (meth)acrylate, "PLACCEL (registered trademark, the same below) FM" (trade name of caprolactone addition monomer manufactured by Daicel Chemical Co., Ltd.), "BLEMMER (registered trademark, the same below) PME-100" (trade name of methoxy polyethylene glycol methacrylate (ethylene glycol chain is 2) manufactured by NOF Corporation), "BLEMMER PME-200" (methoxy polyethylene glycol methacrylate (ethylene glycol chain is 4), trade name, manufactured by NOF Corporation), "BLEMMERPME-400" (methoxy polyethylene glycol methacrylate (ethylene glycol chain is 9), trade name, manufactured by NOF Corporation), "BLEMMER50POEP-800B" (octyloxy polyethylene glycol-polypropylene glycol-methacrylate (ethylene glycol chain is 8, propylene glycol chain is 6), trade name, and "BLEMMER20ANEP-600" (nonylphenoxy (ethylene glycol-polypropylene glycol) monoacrylate, trade name, manufactured by NOF Corporation), "BLEMMER AME-100" (manufactured by NOF Corporation, trade name), "BLEMMER AME-200" (manufactured by NOF Corporation, trade name), and "BLEMMER50AOEP-800B" (manufactured by NOF Corporation, trade name);Trimethylsilyl(meth)acrylate, triethylsilyl(meth)acrylate, tri-n-propylsilyl(meth)acrylate, tri-n-butylsilyl(meth)acrylate, tri-n-pentylsilyl(meth)acrylate, tri-n-hexylsilyl(meth)acrylate, tri-n-octylsilyl(meth)acrylate, tri-n-dodecylsilyl(meth)acrylate, triphenylsilyl(meth)acrylate, tri-p-methylphenylsilyl(meth)acrylate, tribenzylsilyl(meth)acrylate, triisopropylsilyl(meth)acrylate, triisobutylsilyl(meth)acrylate, tri-sec-butylsilyl(meth)acrylate, tri(2-methylisopropyl)silyl(meth)acrylate, tri-tert-butylsilyl(meth)acrylate, ethyldimethylsilyl(meth)acrylate, n-butyldimethylsilyl(meth)acrylate, diisopropyl(n-butyl) 1,2-diisopropylsilyl (meth)acrylate, 1,2-diisopropyl ... Maleate, (tert-butyldiphenylsilyl)(methyl)maleate, (tert-butyldiphenylsilyl)(n-butyl)maleate, (triisopropylsilyl)(methyl)maleate, (triisopropylsilyl)(pentyl)fumarate, (tri-(n-butylsilyl))(n-butyl)fumarate, (tert-butyldiphenylsilyl)(methyl)fumarate, (tert-butyldiphenylsilyl)(n-butyl)fumarate, SILAPLANE FM-0711 (trade name manufactured by JNC), SILAPLANE (registered trademark, the same below) FM-0721 (trade name manufactured by JNC), SILAPLANE FM-0725 (trade name manufactured by JNC), SILAPLANE TM-0701 (trade name manufactured by JNC), SILAPLANE Monomers containing an organosilyl group other than silane coupling agent-containing monomers, such as TM-0701T (manufactured by JNC Corporation, trade name), X-22-174ASX (manufactured by Shin-Etsu Chemical Co., Ltd., trade name), X-22-174BX (manufactured by Shin-Etsu Chemical Co., Ltd., trade name), KF-2012 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name), X-22-2426 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name), and X-22-2404 (manufactured by Shin-Etsu Chemical Co., Ltd., trade name); halogenated olefins such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride, and chlorotrifluoroethylene;2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3,3-pentafluorophenyl (meth)acrylate, 2-(perfluorobutyl)ethyl (meth)acrylate, 3-(perfluorobutyl)2-hydroxypropyl (meth)acrylate, 2-(perfluorohexyl)ethyl (meth)acrylate, 3-perfluorohexyl 2-hydroxypropyl (meth)acrylate, 3-(perfluoro-3-methylbutyl)2-hydroxypropyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, 1H, 1H, 2H, 2H-tridecafluorooctyl (meth) acrylate, 1H-1-(trifluoromethyl) trifluoroethyl (meth) acrylate, 1H, 1H, 3H-hexafluorobutyl (meth) acrylate, 1, 2, 2, 2-tetrafluoro-1-(trifluoromethyl) ethyl (meth) acrylate and other fluorine-containing monomers (but not including halogenated olefins); 1-butoxyethyl (meth) acrylate, 1-(2-ethylhexyloxy) ethyl (meth) acrylate, 1-(cyclohexyloxy) ethyl methacrylate, 2-tetrahydropyranyl (meth) acrylate and other monomers with acetal structures. ;

[0165] In addition, from the perspective of improving the heat resistance and moisture resistance of the polymer composition, the monomer M preferably contains a (meth) acrylate having an alicyclic structure. The alicyclic structure refers to an organic group containing an alicyclic ring, and as an alicyclic group, it can be a monocyclic or polycyclic group. As a monocyclic alicyclic group, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, etc. can be mentioned. In addition, as a polycyclic alicyclic group, norbornyl, isobornyl, tricyclononyl, tricyclodecyl, tetracyclododecyl, etc. can be mentioned. In addition, the hydrogen atoms of these alicyclic groups can also be substituted by alkyl, alkoxy, hydroxyl, etc. As a (meth) acrylate having an alicyclic structure, isobornyl (meth) acrylate is particularly preferred.

[0166] In addition, these monomers may be used in combination of two or more types.

[0167] The weight average molecular weight (Mw) of the compound of the present invention measured by gel permeation chromatography (GPC) is preferably 1000 or more and 100000 or less. From the perspective of improving the holding power when used as a polymer composition, the Mw is preferably higher, but from the perspective of manufacturing stability, it is preferably lower. From the perspective of performance balance, the Mw is more preferably 2000 or more and 50000 or less. In addition, as the compound, a structure represented by the following formula 2 is preferred:

[0168] [Chemistry 6]

[0169]

[0170] In the formula, R is a group having a structure that generates an active species when excited by light, or a linear or branched alkyl group having 1 to 30 carbon atoms, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, or an unsubstituted or substituted heterocyclic group; Z is a terminal group; multiple R 21 Each independently represents a hydrogen atom or a methyl group; multiple R 22 Each independently represents a group having a structure that generates an active species when excited by light, an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, an unsubstituted or substituted heteroaryl group, an unsubstituted or substituted aralkyl group, an unsubstituted or substituted alkaryl group, an unsubstituted or substituted organosilyl group, or an unsubstituted or substituted (poly)organosiloxane group, wherein the substituent in each of these groups is at least one selected from an alkyl group, an aryl group, a heteroaryl group, a non-aromatic heterocyclic group, an aralkyl group, an alkaryl group, a carboxyl group, an alkoxycarbonylalkyl group, an alkylcarbonyloxyalkyl group, an epoxy group, a hydroxyl group, an alkoxy group, a primary amino group, a secondary amino group, a tertiary amino group, an isocyanate group, a sulfonic acid group, and a halogen atom; and n represents a natural number of 2 or more. The terminal group in Z is similar to the terminal group of a polymer obtained by known free radical polymerization, and examples thereof include a hydrogen atom and a group derived from a free radical polymerization initiator.

[0171] In the compound represented by Formula 2, n R 21 and R 22 Here, it is preferred that R or multiple R 22 At least two of them are groups with structures that generate active species when excited by light. For example, the following compounds can be selected: R is a linear or branched alkyl group or alicyclic group having 1 to 30 carbon atoms; 21 Each independently represents a hydrogen atom or a methyl group; multiple R 22 At least two of them are groups having a structure that generates active species when excited by light; the other R 22 Each independently represents a linear or branched alkyl group or alicyclic group having 1 to 30 carbon atoms. Specifically, when n=3, the following compounds can be selected: R is a linear or branched alkyl group or alicyclic group having 1 to 30 carbon atoms; the first to third R 21 is a hydrogen atom or a methyl group; the first R 22 is a linear or branched alkyl group or alicyclic group having 1 to 30 carbon atoms; the second and third R 22 It is a group having a structure that generates active species when excited by light.

[0172] Examples of the structure that generates active species upon light excitation include a benzophenone skeleton, a thioxanthone skeleton, and an anthraquinone skeleton.

[0173] Examples of the group having a structure that generates an active species upon light excitation include a group formed by removing one hydrogen atom from unsubstituted or substituted benzophenone, a group formed by removing one hydrogen atom from unsubstituted or substituted thioxanthone, and a group formed by removing one hydrogen atom from unsubstituted or substituted anthraquinone.

[0174] Examples of these substituents include a linear or branched alkyl group having 1 to 30 carbon atoms, a linear or branched alkoxy group having 1 to 30 carbon atoms, a hydroxyl group, and a halogen atom.

[0175] The linear or branched alkyl group having 1 to 30 carbon atoms is preferably a linear or branched alkyl group having 1 to 20 carbon atoms, more preferably a linear or branched alkyl group having 1 to 10 carbon atoms, and further preferably a linear or branched alkyl group having 1 to 5 carbon atoms.

[0176] Examples of the group derived from the radical polymerization initiator include an alkylcarbonyloxy group having 1 to 30 carbon atoms, a linear or branched alkyl group having 1 to 30 carbon atoms, an arylcarbonyloxy group having 6 to 30 carbon atoms, and an aryl group having 6 to 30 carbon atoms. Examples thereof include 1,1,3,3-tetramethylbutyl and 2-ethylhexylcarbonyloxy groups.

[0177] The unsubstituted or substituted alkyl group is preferably an unsubstituted or substituted straight-chain or branched alkyl group having 1 to 30 carbon atoms, more preferably an unsubstituted or substituted straight-chain or branched alkyl group having 1 to 20 carbon atoms, further preferably an unsubstituted or substituted straight-chain or branched alkyl group having 1 to 10 carbon atoms, and particularly preferably an unsubstituted or substituted straight-chain or branched alkyl group having 1 to 5 carbon atoms.

[0178] The unsubstituted or substituted alicyclic group is preferably an unsubstituted or substituted alicyclic group having 3 to 30 carbon atoms, more preferably an unsubstituted or substituted alicyclic group having 3 to 20 carbon atoms, and still more preferably an unsubstituted or substituted alicyclic group having 3 to 10 carbon atoms.

[0179] The unsubstituted or substituted aryl group is preferably an unsubstituted or substituted aryl group having 6 to 30 carbon atoms, more preferably an unsubstituted or substituted aryl group having 6 to 20 carbon atoms, and still more preferably an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.

[0180] The unsubstituted or substituted heteroaryl group is preferably an unsubstituted or substituted heteroaryl group having 2 to 30 carbon atoms, more preferably an unsubstituted or substituted heteroaryl group having 2 to 20 carbon atoms, and still more preferably an unsubstituted or substituted heteroaryl group having 2 to 10 carbon atoms.

[0181] The unsubstituted or substituted aralkyl group is preferably an unsubstituted or substituted aralkyl group having 6 to 30 carbon atoms, more preferably an unsubstituted or substituted aralkyl group having 6 to 20 carbon atoms, and still more preferably an unsubstituted or substituted aralkyl group having 6 to 10 carbon atoms.

[0182] The unsubstituted or substituted alkaryl group (alkylaryl group) is preferably an unsubstituted or substituted alkaryl group having 6 to 30 carbon atoms, more preferably an unsubstituted or substituted alkaryl group having 6 to 20 carbon atoms, and still more preferably an unsubstituted or substituted alkaryl group having 6 to 10 carbon atoms.

[0183] The unsubstituted or substituted organosilyl group is preferably an unsubstituted or substituted organosilyl group having 1 to 30 carbon atoms, more preferably an unsubstituted or substituted organosilyl group having 1 to 20 carbon atoms, and still more preferably an unsubstituted or substituted organosilyl group having 1 to 10 carbon atoms.

[0184] The unsubstituted or substituted (poly)organosiloxane group is preferably an unsubstituted or substituted (poly)organosiloxane group having 1 to 30 carbon atoms, more preferably an unsubstituted or substituted (poly)organosiloxane group having 1 to 20 carbon atoms, and still more preferably an unsubstituted or substituted (poly)organosiloxane group having 1 to 10 carbon atoms.

[0185] The alkyl group as a substituent is preferably an alkyl group having 1 to 5 carbon atoms. The aryl group as a substituent is preferably an aryl group having 6 to 10 carbon atoms. The heteroaryl group as a substituent is preferably a heteroaryl group having 4 to 10 carbon atoms. The non-aromatic heterocyclic group as a substituent is preferably a non-aromatic heterocyclic group having 5 to 10 carbon atoms. The aralkyl group as a substituent is preferably an aralkyl group having 6 to 10 carbon atoms. The alkaryl group (alkylaryl group) as a substituent is preferably an alkaryl group having 6 to 10 carbon atoms. The alkoxycarbonylalkyl group as a substituent is preferably an alkoxycarbonylalkyl group having 3 to 10 carbon atoms. The alkylcarbonyloxyalkyl group as a substituent is preferably an alkylcarbonyloxyalkyl group having 3 to 10 carbon atoms. The alkoxy group as a substituent is preferably an alkoxy group having 1 to 5 carbon atoms. The secondary amino group as a substituent is preferably a secondary amino group having one alkyl group having 1 to 5 carbon atoms. The tertiary amino group as a substituent is preferably a tertiary amino group having two alkyl groups having 1 to 5 carbon atoms. The halogen atom as a substituent is preferably a fluorine atom, a bromine atom, a chlorine atom or an iodine atom.

[0186] The compound of the present invention can be obtained by polymerizing a monomer mixture containing a monomer M having a free radical polymerizable group by a known method, for example, a method using a cobalt chain transfer agent (U.S. Pat. No. 4,680,352), a method using an α-substituted unsaturated compound such as α-bromomethylstyrene as a chain transfer agent (International Publication No. 88 / 04304), a method of chemically bonding a polymerizable group (Japanese Patent Publication No. 60-133007), and a method using thermal decomposition (Japanese Patent Publication No. 11-240854). Among these, the method using a cobalt chain transfer agent is preferred from the perspective of using a catalyst with a small number of production steps and a high chain transfer constant.

[0187] A compound comprising two or more structural units derived from a monomer M having a free radical polymerizable group and having a free radical polymerizable group A at the end, wherein the monomer M comprises a monomer m, and the monomer m has a structure that generates an active species when excited by light, and for the compound, whether the compound contains the structure is confirmed by an analytical method such as nuclear magnetic resonance (NMR).

[0188] For example, when the terminal free radical polymerizable group A has an unsaturated hydrocarbon structure such as CH2=C-, it can be measured by using a proton nuclear magnetic resonance apparatus with deuterated chloroform as the solvent and the nucleus as the measuring core: 1 H, measurement temperature: 35°C, cumulative number of times: 1024 times. The chemical shift during the measurement was within the range of 4ppm to 7ppm. In addition, for the structure derived from the monomer m having a structure that generates active species upon photoexcitation, for example, when having an aromatic hydrocarbon structure, the peak derived from the unsaturated hydrocarbon structure can be determined by using a proton nuclear magnetic resonance apparatus with a solvent of deuterated chloroform and a measurement nucleus of: 1 H. Measurement temperature: 35° C., cumulative number of times: 1024 times. A peak derived from an aromatic hydrocarbon structure was confirmed in the range of 6 ppm to 9 ppm during the measurement.

[0189] The compound of the present invention contains two or more structural units derived from a monomer M having a radical polymerizable group and has a radical polymerizable group A at the terminal, and thus can be used as a monomer for synthesizing a polymer, and is also called a macromonomer.

[0190] 《Polymer composition》

[0191] The compound of the present invention can be mixed with other polymers (hereinafter, also referred to as "polymers") other than the compound and used as a polymer composition. The polymer composition forms a cross-linked structure with the polymer through the free radical polymerizable group A at the end of the compound of the present invention and the structure of generating active species by light excitation, thereby improving the cohesion of the polymer composition.

[0192] <Polymer>

[0193] The polymer contained in the polymer composition of the present invention substantially does not have a radical polymerizable group A at the terminal.

[0194] The polymer may be a polymer of a single monomer (homopolymer) or a copolymer of multiple monomers (copolymer). In addition, the polymer may be any of a random copolymer, a block copolymer or a graft copolymer.

[0195] In addition, the polymer is preferably a polymer for adhesives. By irradiating the polymer composition with ultraviolet rays or the like to form a crosslinked structure, the adhesive force, holding power, and substrate stain resistance of the polymer composition are improved.

[0196] From the perspective of melt viscosity, the glass transition temperature of the polymer is preferably 0°C or less, more preferably -10°C or less. Specifically, the glass transition temperature of the polymer is preferably -100 to 0°C, more preferably -80 to -5°C. It should be noted that the glass transition temperature (Tg) is a value calculated by the following formula after the absolute temperature (K) is converted into Celsius (°C).

[0197] 1 / Tg=Σ(w i / Tg i )

[0198] In the above formula, w i represents the mass fraction of monomer i constituting the polymer, Tg i It represents the glass transition temperature of the homopolymer of monomer i constituting the polymer.

[0199] Tg and Tg in the above formula i It is a value expressed by absolute temperature (K). In addition, the glass transition temperature of the homopolymer of monomer i is a value described in Polymer Handbook [Polymer HandBook, J. Brandrup, Interscience, 1989].

[0200] Furthermore, from the viewpoint of adhesive properties, the polymer is preferably a (meth)acrylic copolymer.

[0201] The (meth)acrylic copolymer is a copolymer in which at least a part of the structural units are structural units derived from (meth)acrylic monomers. The (meth)acrylic copolymer may further include structural units derived from monomers other than (meth)acrylic monomers (eg, styrene, etc.).

[0202] The (meth)acrylic monomer is a monomer having a (meth)acryloyl group, and examples thereof include the same (meth)acrylic monomers as those constituting the compound of the present invention.

[0203] In order to improve adhesive force, the (meth)acrylic copolymer preferably includes a structural unit derived from a carboxyl group-containing (meth)acrylic monomer.

[0204] Examples of the carboxyl-containing (meth)acrylic monomer include (meth)acrylic acid, 2-(meth)acryloxyethylhexahydrophthalic acid, 2-(meth)acryloxypropylhexahydrophthalic acid, 2-(meth)acryloxyethylphthalic acid, 2-(meth)acryloxypropylphthalic acid, 2-(meth)acryloxyethylmaleic acid, 2-(meth)acryloxypropylmaleic acid, 2-(meth)acryloxyethylsuccinic acid, and 2-(meth)acryloxypropylsuccinic acid.

[0205] The content of the structural unit derived from the carboxyl group-containing (meth)acrylic monomer is preferably 0.1 to 20% by mass, more preferably 0.5 to 10% by mass, and more preferably 1 to 6% by mass, based on the total mass of the (meth)acrylic copolymer.

[0206] Furthermore, from the perspective of improving the cohesive force of the polymer composition, the (meth)acrylic copolymer is preferably capable of forming a crosslinked structure, and from the perspective of improving the holding power when used as a polymer composition, it is more preferable to contain a structural unit derived from a monomer having the following structure that generates free radicals when excited by light.

[0207] [Chemistry 7]

[0208]

[0209] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group.

[0210] In addition, the weight average molecular weight (Mw) of the (meth)acrylic copolymer measured by gel permeation chromatography (GPC) is preferably 5000 to 2000000, more preferably 10000 to 1000000, and further preferably 30000 to 350000. When the Mw is above the lower limit, the durability of the adhesive layer is excellent, and when it is below the upper limit, the workability (compatibility with other components, coating properties, hot melt processability, etc.) is excellent.

[0211] Furthermore, from the viewpoint of adhesive properties, the glass transition temperature (Tg) of the (meth)acrylic copolymer is preferably 0°C or less, more preferably -5°C or less. Specifically, the glass transition temperature of the polymer is preferably -100°C or more and 0°C or less, more preferably -80°C or more and -5°C or less.

[0212] The (meth)acrylic copolymer can be produced by using a known polymerization initiator and a known method. As the polymerization method, for example, known polymerization methods such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be applied, and solution polymerization is preferred.

[0213] The polymer composition of the present invention may be a mixture of the above-mentioned binder polymer and the compound of the present invention, or may be a mixture of the polymer of the present invention and the compound.

[0214] In the polymer composition, the ratio (mass ratio) of the compound to the polymer is preferably in the range of 1:3 to 0.5:99.5, and more preferably 1:9 to 1:70.

[0215] The polymer composition of the present invention may also contain other components. As other components, known components may be used, for example, solvents, fillers, crosslinking agents, tackifying resins, antioxidants, light stabilizers, metal deactivators, anti-aging agents, moisture absorbents, rust inhibitors, anti-hydrolysis agents, and reaction catalysts.

[0216] Examples of the antioxidant include phenol-based, phosphorus-based, hydroxylamine-based, and sulfur-based antioxidants.

[0217] The polymer composition of the present invention can be used as a liquid adhesive composition containing a solvent, or can be used as a hot-melt adhesive composition not containing a solvent.

[0218] The polymer composition of the present invention can be used as an adhesive by curing it with active energy rays as needed. As active energy rays, ultraviolet rays are preferred from the perspective of versatility. As the light source of ultraviolet rays, for example, xenon lamps, high-pressure mercury lamps, metal halide lamps, etc. can be mentioned.

[0219] When an adhesive layer is formed from the polymer composition of the present invention, the melt viscosity when measured at 130° C. and a frequency of 0.02 Hz is preferably 10 to 300 Pa·s, more preferably 20 to 200 Pa·s.

[0220] When an adhesive layer is formed from the polymer composition of the present invention, the peel strength (N / 25 mm) is preferably 5 to 20 N / 25 mm, more preferably 10 to 17 N / 25 mm.

[0221] When an adhesive layer is formed from the polymer composition of the present invention and bonded to a SUS plate, and a load of 1.0 kg is applied downward at 40° C., the holding time is preferably 50,000 seconds or more, more preferably 86,400 seconds or more.

[0222] The adhesive layer formed from the polymer composition of the present invention is bonded to a SUS plate, and the holding time when a load of 1.0 kg is applied downward to the other side of the adhesive layer at 80°C is preferably 1500 seconds or more, more preferably 3000 seconds or more, and further preferably 20000 seconds or more.

[0223] The adhesive layer is formed from the polymer composition of the present invention and adhered to a SUS plate. When the adhesive layer is peeled off, the residual adhesive area relative to the surface area of ​​the SUS plate is preferably 0 area % or more and less than 20 area %, more preferably 0 area %.

[0224] 《(Meth)acrylic acid copolymer》

[0225] The (meth)acrylic copolymer of the present invention includes a structural unit derived from a monomer m having a structure that generates an active species when excited by light. The polymer contained in the (meth)acrylic copolymer of the present invention does not substantially have a radical polymerizable group A at the terminal.

[0226] As the monomer m, the same monomers as those described above in the <<Compound>> can be used.

[0227] As the (meth)acrylic copolymer of the present invention, as the structural unit other than the structural unit derived from the monomer m, the same structural units as those described above in <Polymer> can be used.

[0228] 《Polymer composition》

[0229] The (meth)acrylic copolymer of the present invention including the structural unit derived from the monomer m can be mixed with a compound having a free radical polymerizable group A at the terminal and used as a polymer composition. The polymer composition forms a crosslinked structure through the structure of the active species generated by the free radical polymerizable group A at the terminal of the compound and the (meth)acrylic copolymer of the present invention when excited by light, thereby improving the cohesive force of the polymer composition.

[0230] <Compound>

[0231] The compound contained in the polymer composition of the present invention has a radical polymerizable group A at the terminal.

[0232] As the compound, the above-mentioned macromonomer is preferred. The macromonomer may or may not contain a structural unit derived from a monomer m, and the monomer m has a structure that generates an active species when excited by light.

[0233] Adhesive Sheet

[0234] The adhesive sheet of the present invention has an adhesive layer formed using the adhesive composition. The adhesive sheet may be a sheet consisting only of an adhesive layer formed by molding the adhesive composition of the present invention into a sheet, or may be a sheet formed by laminating a releasable substrate on one or both sides of an adhesive layer formed by molding the adhesive composition of the present invention into a sheet.

[0235] <Adhesive layer>

[0236] The adhesive layer may be composed of the adhesive composition of the present invention or a cured product of the adhesive composition of the present invention. From the perspective of the handleability of the adhesive sheet, the adhesive layer is preferably composed of an adhesive obtained by curing the adhesive composition of the present invention with ultraviolet rays.

[0237] The thickness of the adhesive layer can be appropriately set according to the application. For example, it is preferably 10 to 500 μm, and more preferably 20 to 100 μm. The thickness can be measured by a method using a constant pressure thickness measuring instrument, or by adjusting the thickness of the coating film and the solid content of the composition.

[0238] The parts to be bonded using the adhesive composition of the present invention are not particularly limited, and can be used, for example, for bonding window films on vehicles and buildings, bonding labels on labels, bonding various panels such as liquid crystal panels, and bonding transparent plates such as glass.

[0239] Example

[0240] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples. Hereinafter, "parts" means "parts by mass". Evaluation was performed by the following method.

[0241] <Molecular Weight of Compound Containing Two or More Structural Units Derived from Monomer M>

[0242] The determination was performed using a gel permeation chromatography (GPC) apparatus (manufactured by Tosoh Corporation, HLC-8320). A 0.2 mass % tetrahydrofuran (THF) solution of the compound was prepared, and 10 μL of the solution was injected into the apparatus equipped with a chromatographic column manufactured by Tosoh Corporation (TSKgel SuperHZM-M×HZM-M×HZ2000, TSKguardcolumn SuperHZ-L), and the determination was performed under the conditions of flow rate: 0.35 mL / min, eluent: THF (stabilizer: butylated hydroxytoluene (BHT)), and column temperature: 40°C. The number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated by conversion to polystyrene.

[0243] <Molecular weight of polymer>

[0244] The measurement was performed using a GPC device (manufactured by Tosoh Corporation, HLC-8120). A 0.3 mass % THF solution of the polymer was prepared, and 20 μL of the solution was injected into the above device equipped with a chromatographic column manufactured by Tosoh Corporation (TSKgel SuperHM-H×4, TSKguardcolumn SuperH-H), and the measurement was performed under the conditions of flow rate: 0.6 mL / min, eluent: THF (stabilizer BHT), and column temperature: 40°C. The number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated by conversion to polystyrene.

[0245] <Preparation of test pieces>

[0246] The polymer was diluted with ethyl acetate so that the solid content of the composition was 33.3%, and then the compound was added and mixed. It was visually confirmed that no dissolved compound remained, thereby preparing a polymer composition that was liquid at room temperature (23°C).

[0247] The polymer composition was applied on a PET film having a thickness of 38 μm using an applicator and dried at 90° C. for 1 hour to form an adhesive layer.

[0248] The PET film (PET) forming the adhesive layer was irradiated with ultraviolet light in air using a 90mW high-pressure mercury lamp to cure the adhesive layer. The irradiation energy was 35mJ / cm 2 or 105mJ / cm 2 (Measured value using an ultraviolet energy meter UV POWER PUCK II (S / N 13685) (manufactured by EIT Corporation, USA)) A release-treated PET film (release PET) was stacked thereon to obtain a laminate having a release PET-adhesive layer-PET structure.

[0249] The thickness of the adhesive layer was 50 μm. The cured laminate was cut into strips of 25 mm in width and 250 mm in length to prepare test pieces.

[0250] <Melt Viscosity>

[0251] The polymer composition was applied with an applicator and dried at 90°C for 1 hour. The adhesive layer was measured using a HAAKE MARS viscoelastic property measuring device. The viscosity (η) when measured at 130°C and a frequency of 0.02 Hz using a cone plate with a diameter of 35 mm was * ) value was taken as the value of the melt viscosity at 130°C.

[0252] <Adhesion>

[0253] The PET of the peeling test piece was peeled off to expose the adhesive layer, and it was laminated to a 30 mm × 110 mm stainless steel (SUS) plate using a 3 kg hand roller so that the laminating surface was 25 mm × 70 mm. The peel strength (N / 25 mm) relative to the SUS plate was measured at a peeling angle of 180° and a tensile speed of 300 mm / min as the adhesive force.

[0254] <Retention force>

[0255] On one side of the test piece, peel off the PET to expose the adhesive layer, and use a 3kg hand roller to horizontally bond it to a 30mm×110mm SUS plate with a bonding surface of 25×25mm. Place it in a constant temperature and humidity layer tester at a temperature of 40℃ or 80℃ and a humidity of 35% for 15 minutes. Immediately thereafter, set the SUS plate in a manner that a force is applied to the bonding surface in the shear direction, apply a load of 1.0kg downward on the other side of the test piece, and measure the holding time as the holding force.

[0256] <Base material anti-fouling properties>

[0257] The PET of the test piece was peeled off to expose the adhesive layer, and it was laminated on a 30 mm × 110 mm SUS plate with a 3 kg hand roller so that the laminating surface was 25 mm × 70 mm. Then, the test piece was peeled off under the same conditions as the evaluation method of the adhesive strength, and the SUS surface was visually observed to determine the substrate anti-contamination property according to the following standards.

[0258] A: No residual glue (the ratio of the residual glue area to the surface area of ​​the SUS plate is 0 area %);

[0259] B: The proportion of residual adhesive area is greater than 0 area % and less than 30 area %;

[0260] C: The ratio of the residual adhesive area is 30 area % or more.

[0261] In addition, the presence or absence of residual adhesive was confirmed by visual inspection.

[0262] <Production Example 1 [Dispersant 1]>

[0263] In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer and a nitrogen inlet tube, 900 parts of deionized water, 60 parts of sodium methacrylate 2-ethanesulfonate, 10 parts of potassium methacrylate and 12 parts of methyl methacrylate (MMA) were added and stirred, and the temperature was raised to 50° C. while nitrogen substitution was performed in the polymerization apparatus. 0.08 parts of 2,2'-azobis(2-methylpropylamidine) dihydrochloride as a polymerization initiator was added, and the temperature was raised to 60° C. After the temperature was raised, MMA was continuously added dropwise at a rate of 0.24 parts / min for 75 minutes using a dropping pump. The mixture was kept at 60° C. for 6 hours and then cooled to room temperature to obtain a dispersant 1 having a solid content of 10% by mass.

[0264] <Production Example 2 [Chain Transfer Agent 1]>

[0265] In a synthesis apparatus equipped with a stirring device, 1.00 g of cobalt acetate (II) tetrahydrate, 1.93 g of diphenylglyoxime, and 80 mL of diethyl ether previously deoxygenated by nitrogen bubbling were added under a nitrogen atmosphere, and stirred at room temperature for 30 minutes. 10 mL of boron trifluoride diethyl ether complex was then added, and stirred for 6 hours. The mixture was filtered, the solid was washed with diethyl ether, and vacuum dried for 15 hours to obtain 2.12 g of chain transfer agent 1 as a reddish brown solid.

[0266] <Production Example 3 [Compound M-1]>

[0267] In a polymerization apparatus equipped with a stirrer, a cooling tube, a thermometer, and a nitrogen inlet tube, 145 parts of deionized water, 0.1 parts of sodium sulfate, and 0.25 parts of dispersant 1 (solid content 10% by mass) were added and stirred to prepare a uniform aqueous solution. 100 parts of MMA, 0.0022 parts of chain transfer agent 1, and 0.4 parts of PEROCTA (registered trademark) O (1,1,3,3-tetramethylbutyl peroxy 2-ethylhexanoate, manufactured by NOF Corporation) as a polymerization initiator were added to prepare an aqueous suspension.

[0268] Further, the polymerization device was purged with nitrogen and heated to 80°C and stirred for 3.5 hours. To further increase the polymerization rate, the temperature was raised to 90°C and maintained for 1 hour. Then, the mixture was cooled to 40°C to obtain an aqueous suspension containing the compound. The obtained aqueous suspension was filtered with a filter, and the residue remaining on the filter was washed with deionized water and dehydrated, and dried at 40°C for 16 hours to obtain compound M-1. The molecular weight measurement results are shown in Table 1.

[0269] <Production Examples 4 to 10 [Compounds M-2 to M-8]>

[0270] Compounds M-2 to M-8 were prepared in the same manner as in Preparation Example 3 except for the changes in formulation shown in Table 1. The formulation unit shown in Table 1 is parts by mass.

[0271] [Table 1]

[0272]

[0273] <Production Example 11 [(Meth)acrylic Copolymer A-1]>

[0274] In a four-necked flask equipped with a stirrer, a thermometer, a cooling tube, and a nitrogen inlet, 40 parts of ethyl acetate and 7.7 parts of isopropyl alcohol (IPA) were added, and the external temperature was raised to 85°C while nitrogen was introduced. After the external temperature reached 85°C and the internal temperature was stabilized, a mixture of 25 parts of ethyl acetate, 95 parts of n-butyl acrylate (n-BA), 5 parts of acrylic acid (AA), and 0.13 parts of NYPER (registered trademark) BMT-K40 (manufactured by NOF Corporation, trade name) was added dropwise over 4 hours. After the addition was completed, the mixture was kept for 1 hour, and then a mixture of 0.5 parts of PEROCTA O and 10 parts of ethyl acetate was added over 30 minutes. Then, after keeping it for 2 hours, 0.5 parts of an antioxidant (manufactured by BASF, trade name "IRGANOX (registered trademark) 1010") was added, and ethyl acetate was added to make the solid content (the ratio of the monomer charge amount in the (monomer + solvent charge amount)) 53% by mass, and then cooled to room temperature to obtain a copolymer solution A-1 containing the (meth)acrylic copolymer A-1.

[0275] [Table 2]

[0276]

[0277] <Production Examples 12 and 13>

[0278] Except for changing the composition as shown in Table 2, a copolymer solution A-2 containing the (meth)acrylic copolymer A-2 and a copolymer solution A-3 containing the (meth)acrylic copolymer A-3 were obtained in the same manner as in Production Example 11.

[0279] <Examples 1 to 16, Comparative Examples 1 to 3>

[0280] Using the polymer compositions obtained by blending the polymers and compounds shown in Tables 3 and 4, test pieces were prepared by the above method and the adhesive force, holding power and substrate anti-fouling property were evaluated. The evaluation results are shown in Tables 3 and 4.

[0281] For explanation, the symbols in each table are as follows:

[0282] MMA: Methyl Methacrylate

[0283] IBXMA: Isobornyl methacrylate

[0284] IBMA: Isobutyl Methacrylate

[0285] IPA: Isopropyl alcohol

[0286] n-BA: n-butyl acrylate

[0287] AA: Acrylic acid

[0288] m1: 4-methacryloyloxybenzophenone

[0289] m2: 4-[2-(methacryloyloxy)ethoxy]benzophenone

[0290] It was confirmed that the polymer compositions of Examples 1 to 16 were superior in adhesive force, holding power, and stain resistance compared to the polymer compositions of Comparative Examples 1 to 3.

[0291] Since the compound of the present invention was not formulated in Comparative Example 1, the adhesive force, holding power and substrate anti-fouling property were insufficient.

[0292] Since only the monomer having a structure that generates active species upon light excitation was formulated in Comparative Example 2, the adhesive force and the holding force were insufficient.

[0293] Since the compound in Comparative Example 3 has a radical polymerizable group A at the terminal and does not have a structural unit derived from a monomer having a structure that generates an active species upon photoexcitation, the holding power and substrate anti-fouling property are insufficient.

[0294] [Table 3]

[0295]

[0296] [Table 4]

[0297]

[0298] Industrial Applicability

[0299] When used as a component of a polymer composition, the compound of the present invention improves adhesion, holding power, and substrate stain resistance.

Claims

1. A polymer composition comprising a compound comprising two or more structural units derived from a monomer M having a free radical polymerizable group and having a free radical polymerizable group A at a terminal, and polymers other than said compounds, in, The monomer M includes a monomer m, and the monomer m has a structure that generates an active species when excited by light. The monomer m has a structure represented by the following formula 1; [Chemistry 1] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group, The compound has a structure represented by the following Formula 2: [Chemistry 2] In the formula, R is a group having a structure that generates an active species when excited by light, or a linear or branched alkyl group having 1 to 30 carbon atoms, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, or an unsubstituted or substituted heterocyclic group; Z is a terminal group; multiple R 21 Each independently represents a hydrogen atom or a methyl group; multiple R 22 Each independently represents a group having a structure that generates an active species when excited by light, an unsubstituted or substituted alkyl group, an unsubstituted or substituted alicyclic group, an unsubstituted or substituted aryl group, an unsubstituted or substituted heteroaryl group, an unsubstituted or substituted aralkyl group, an unsubstituted or substituted alkaryl group, an unsubstituted or substituted organosilyl group, or an unsubstituted or substituted (poly)organosiloxane group, wherein the substituents in these groups are at least one selected from an alkyl group, an aryl group, a heteroaryl group, a non-aromatic heterocyclic group, an aralkyl group, an alkaryl group, a carboxyl group, an alkoxycarbonylalkyl group, an alkylcarbonyloxyalkyl group, an epoxy group, a hydroxyl group, an alkoxy group, a primary amino group, a secondary amino group, a tertiary amino group, an isocyanate group, a sulfonic acid group, and a halogen atom; n represents a natural number of 2 or more, The polymer other than the above compound contains a structural unit derived from a carboxyl group-containing (meth)acrylic monomer, has a glass transition temperature of 0° C. or less, The glass transition temperature Tg is the value converted to Celsius degrees from the absolute temperature K calculated by the following formula: 1 / Tg=Σ(in i / Tg i ), In the above formula, w i represents the mass fraction of monomer i constituting the polymer, Tg i The glass transition temperature, Tg, and Tg i It is a value expressed by absolute temperature K. In addition, the glass transition temperature of the homopolymer of monomer i is a value described in Polymer Handbook [Polymer HandBook, J. Brandrup, Interscience, 1989].

2. The polymer composition according to claim 1, wherein The active species generated by light excitation are free radicals.

3. The polymer composition according to claim 1 or claim 2, wherein: The content of the structural unit derived from the monomer m in the compound is 0.01% by mass or more and 50% by mass or less relative to the total mass of the compound.

4. The polymer composition according to claim 1 or claim 2, wherein: The monomer M includes a (meth)acrylate having an alicyclic structure.

5. The polymer composition according to claim 1 or claim 2, wherein: The weight average molecular weight measured by gel permeation chromatography is 1,000 or more and 100,000 or less.

6. The polymer composition according to claim 1 or 2, wherein The polymer has a glass transition temperature of -100°C or higher and 0°C or lower.

7. The polymer composition according to claim 1 or 2, wherein The polymer is a (meth)acrylic copolymer.

8. The polymer composition according to claim 1 or 2, wherein The polymer is a (meth)acrylic copolymer including a structural unit derived from a monomer m, wherein the monomer m has a structure that generates an active species when excited by light.

9. The polymer composition according to claim 7, wherein The (meth)acrylic copolymer comprises a structural unit derived from a monomer represented by the following Formula 1; [Chemistry 3] In the formula, R A , R B Each independently represents an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group or a halogen atom; n represents an integer of 0 to 5; m represents an integer of 0 to 4; and X represents a (meth)acryloyloxy group or a (meth)acryloyloxyalkyleneoxy group. 10 . An adhesive composition comprising the polymer composition according to claim 1 . 11 . An adhesive obtained by irradiating the adhesive composition according to claim 10 with ultraviolet rays.

12. An adhesive sheet having an adhesive layer, wherein: The adhesive layer comprises the adhesive composition according to claim 10 .

13. An adhesive sheet having an adhesive layer, wherein: The adhesive layer includes the adhesive irradiated with ultraviolet rays according to claim 11.

Citation Information

Patent Citations

  • Preparation of macromonomer

    JP1985133007A

  • Production of oligomer

    JP1999240854A

  • Radiation curable pressure sensitive adhesive sheet

    JP2013040256A

  • Insulated wire

    JP2020053216A

  • Cobalt (II) chelates as chain transfer agents in free radical polymerizations

    US4680352A